Score reproducibility and reliability in differentiating small bowel subepithelial masses from innocent bulges. Issue 10 (October 2022) - Sciberras, Martina; Conti, Kelly; Elli, Luca; Scaramella, Lucia; Riccioni, Maria Elena; Marmo, Clelia; Cadoni, Sergio; McAlindon, Mark; Sidhu, Reena; O'hara, Fintan; McNamara, Deirdre; Rondonotti, Emanuele; et al.
Abstract: Aims: The primary aim of this study was to assess the reliability, intra- and inter-observer variation of the SPICE, Mucosal protrusion angle (MPA) and SHYUNG scores in differentiating a subepithelial mass (SEM) from a bulge. Methods: This retrospective multicentre study analysed the 3 scores, radiological studies, enteroscopy and/or surgical findings. Results: 100 patients with a potential SEM (mean age 57.6years) were recruited with 75 patients having pathology. In patients with a SEM the mean SPICE score was 2.04 (95% CI 1.82–2.26) as compared to 1.16 (95% CI 0.81–1.51) without any pathology (AUC 0.74, p <0.001), with a fair intra-observer agreement (Kappa 0.3, p <0.001) and slight inter-observer agreement (Kappa 0.14, p <0.05). SPICE had a 37.3% sensitivity and 92.0% specificity in distinguishing between a SEM and bulge, whereas MPA<90˚ had 58.7% and 76.0% respectively, with poor intra-observer( p = 0.05) and interobserver agreement ( p = 0.64). The SHYUNG demonstrated a moderate intra-observer (Kappa 0.44, p <0.001) and slight inter-observer reliability (Kappa 0.18, p <0.001). The sensitivity of an elevated SHYUNG score (≥4) in identifying a SEM was 18.7% with a specificity of 92.0% (AUC 0.71, p = 0.002). Conclusions: Though these scores are easy to use, they have, at best, slight to moderate intra and inter-observer agreement. Their overall diagnostic performances are limited.